Soil Microbial Communities Associated With Biodegradable Plastic Mulch Films - Bandopadhyay, Sreejata; Liquet y González, José E.; Henderson, Kelsey B.; Anunciado, Marife B.; Hayes, Douglas G.; DeBruyn, Jennifer M. (Frontiers in Microbiology, 2020)
Agricultural plastic mulch films provide a favorable soil microclimate for plant growth, improving crop yields. Biodegradable plastic mulch films (BDMs) have emerged as a sustainable alternative to widely used non-biodegradable polyethylene (PE) films. BDMs are tilled into the soil after use and are expected to biodegrade under field conditions. However, little is known about the microbes involved in biodegradation and the relationships between microbes and plastics in soils. In order to capture the consortium of soil microbes associated with (and thus likely degrading) BDMs, agriculturally-weathered plastics from two locations were studied alongside laboratory enrichment experiments to assess differences in the microbial communities associated with BDMs and PE. Using a combination of amplicon sequencing and qPCR, we observed that agriculturally-weathered plastics hosted an enrichment of fungi and an altered bacterial community composition compared to the surrounding soil. Notably, Methylobacterium, Arthrobacter, and Sphingomonas were enriched on BDMs compared to non-biodegradable PE. In laboratory enrichment cultures, microbial consortia were able to degrade the plastics, and the composition of the microbial communities was influenced by the composition of the BDMs. Our initial characterization of the microbial communities associated with biodegradable plastic mulch films, or the biodegradable “plastisphere”, lays the groundwork for understanding biodegradation dynamics of biodegradable plastics in the environment.